EDUKASI TEKNOLOGI BUDI DAYA HIDROPONIK BAGI MASYARAKAT DESA PAJANGAN SUKODADI LAMONGAN - Choirul Anam; Mariyatul Qibtiyah; Ghadry Salsabila Cahyani; M. Nuri; M. Sunarto; Arga Ardhiansyah (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
This service activity aims to provide real learning and practice for the youth organizations of Pajangan village, Sukodadi Lamongan, regarding the practice of good hydroponic farming practices. This activity uses training methods on the methods and practices of hydroponic farming; technical assistance in the field regarding the assembly of hydroponic media; and farming, from making nutrient solutions, sowing seeds, planting, to harvesting; and field visits. Participants were able to take part in the activities properly regarding the material provided and guidance on assembling the installation and how to plant hydroponically. The level of satisfaction and benefits of participants in participating in this training reached a score of 9.15. This activity made the participants desire to be entrepreneurs in the field of hydroponics. The condition of the harvested plants is sufficient to provide the expected results. In order for this activity to continue and have a better impact, it is hoped that the Pajangan village can facilitate so that the participants of this activity can transmit their knowledge to other people who want to become hydroponic entrepreneurs.